Evolving time-varying market efficiency of energy stock market - Fazlollahi, Negar; Ozatac, Nesrin; Gokmenoglu, Korhan K. (Springer Heidelberg, 2020)
Energy stocks have become an essential segment of the investment portfolios of both households and institutional investors. This study investigates the dynamic aspect of evolving weak-form efficiency in six energy stock markets: those of the United States (US), Canada, China, Australia, India, and Saudi Arabia. The generalized autoregressive conditionally heteroskedastic in the mean GARCH-M(1,1) method is applied, alongside the state-space time-varying approaches with the Kalman filter estimation, to detect the evolving efficiency for periods ending in November 2019. The empirical results reveal that the studied markets undergo various extents of time-varying efficiency, containing periods of efficiency enhancement as well as periods of deviation from efficiency. Meanwhile, the 2007-2009 global financial crisis and the 2015 changes in the energy sector-in addition to other contemporaneous crises-have a profound influence on the timeline of market efficiency evolution. Overall, all of the markets gradually became more efficient, apart from India's energy market as a result of the current energy crisis in India. Amid the energy markets explored in this study, the US energy market was found to be the most efficient.
Keywords: Energy stock market; GARCH-M; Time-varying efficiency; Kalman filter